A Companion to Renaissance Drama. - Kinney, Arthur (Blackwell companions to literature and culture, 2007)
An expansive and interdisciplinary guide to Renaissance plays and the world they played to, covering: the meaning of works by playwrights such as Marlowe and Jonson; why the plays do or say what they do; and what the plays may have said to Tudor and Stuart playgoers.